CHARACTERISTICS OF LUNG FOCI REVEALED BY COMPUTED TOMOGRAPHY IN HIGH-RISK CHILDREN AND ADOLESCENTS FOR TUBERCULOSIS - L. P. Shepeleva; V. A. Aksenova; I. E. Tyurin (Вестник рентгенологии и радиологии)
Objective: to give an X-ray pattern of single lung foci revealed by computed tomography (CT) in children and adolescents examined for tuberculosis. Material and methods. The results of CT in 52 children and adolescents infected by Mycobacterium tuberculosis were analyzed. All the followed up children and adolescents underwent X-ray study using a two-slice spiral Somatom Emotion Duo (Siemens). The study used first the conventional chest spiral CT scanning procedure for children according to the Thorax Routine program and then reconstruction. Target spiral scanning of the area of interest was, if needed, carried out by employing high resolution CT with 2-mm thick images taken at 1.5-mm spacing. A maximal intensity project program was used to separate vessels and foci. Results. The single foci were encountered frequently in the lung of the examinees and characterized by a perilymphatic site; in 88.0% they were connected with the interlobular interstitium, interlobar fissure, and paracostal pleura; in 92.2% the foci were detectable in the subpleural and cortical parts of the lung, had a moderate intensity, well-defined outlines, and were 2–6 mm in size. At the same time, there were no pathological changes in the lymph nodes of the lung roots and mediastinum. The long-term (2-month-to-5-year) followup in this group of children indicated that there were no X-ray changes in the lung foci revealed by CT. Conclusion. The single foci in the lung of Mycobacterium tuberculosis-infected children without X-ray changes in the lymph nodes of the lung roots and mediastinum may be manifestations of the normal lung structure – these may be intrapulmonary lymph nodes. Further follow-up in this group of these children must be in agreement with the management tactics of those infected with Mycobacterium tuberculosis.